A cross-sectional study on the secondary school students’ subjective happiness and attitudes towards mathematics - Mamolo, Leo A.; Labina, Charlie S. (Journal of Education and Learning (EduLearn), 2025)
Students’ subjective happiness and attitudes toward learning a subject matter are two factors that could affect learning. These variables are essential for successful instruction. This study ascertained students’ subjective happiness and attitudes towards mathematics of secondary school students grouped according to different variables and their relationship. The correlation of the two variables was also determined. Descriptive-correlational research was utilized in the study, and 300 randomly chosen students were chosen as participants. Using two adopted questionnaires, results showed a less happy student compared to the average person and a moderate level of attitude towards mathematics. These results are the same for all variables involved in the study, like sex, year level, family monthly income, daily allowance, and other variables. Results further showed a weak but significant positive correlation between the two variables involved. This suggests that the students’ level of happiness may be a potential factor that can influence their attitudes toward mathematics. School stakeholders may find ways to improve students’ well-being, happiness, and attitude, which could, in turn, improve mathematics performance.